Integration of IoT in building energy infrastructure: A critical review on challenges and solutions. (March 2023) - Moudgil, Vipul; Hewage, Kasun; Hussain, Syed Asad; Sadiq, Rehan
Abstract: The Internet of Things (IoT) has unprecedentedly entangled the physical world with cyber technologies and its integration with building infrastructure (BI) is no different. Integration of IoT can impart BI with upscale features like remote operations, automated management and user-centric facilities by developing an interconnected cognitive building (CB) ecosystem. However, this integration has entered an ambiguous phase of realizing mature adoption and practical utilization of IoT in BI for both academic and industrial domains. This ambiguity restricts the IoT and BI stakeholders to comprehend and acknowledge the full operational competency of IoT in BI. Thus, a significant research gap exists that deeply investigates the practical implementation and mature adoption of IoT in BI. The prime objective of this study is to establish a comprehensive review by exploring the state-of-art academic, technological and industrial research to identify major technological and behavioural interventions that successfully enhance the integration of IoT in BI. Besides, this study also highlights significant technical and non-technical challenges that require substantial research efforts for maturing the adoption of IoT in BI. The findings of the study argue that the full operational competency of IoT in BI is not yet realized and a dedicated effort from both IoT and BI stakeholders is required to provide modern BI with a generic IoT framework having cognitive intelligence and context-aware computing capabilities. The proposed study will assist the researchers in realizing the full operational competency of IoT in BI for more exciting innovations. Highlights: Adoption and implementation of IoT in building infrastructure are investigated. Technological and behavioural interventions for cognitive intelligence in buildings. Requirement of a seamlessly unified IoT framework for future buildings. Trends, challenges and future research to effectively implement IoT in buildings.